Preserving and Optimising a World-Class African Ornithological Collection - Mashao, Mmatjie; Allan, David (Biodiversity Information Science and Standards, 2018)
The Durban Natural Science Museum houses a world-class collection of African bird study skins and other ornithological specimens including eggs, nests, skeletons, open wings and ethanol specimens. This presentation briefly outlines the value of these holdings. The bird study skins comprise the core of the collection and number nearly 40 000. This ranks the collection as one of the top three or four on the continent. These study skins are globally renowned for the quality of their preparation, far exceeding that of other African museums. The study skin collection houses an unparalleled assemblage of holotypes and paratypes of (mainly) southern African subspecies. A recent landmark book on geographical variation in southern African birds was largely based on examination of this collection. The collection also boasts the largest collection of study skins in existence from Mozambique. The collection includes one of the most significant Dodo Raphus cucullatus skeletons in the world, which has been subject to intense investigation in recent years, as well as a complete egg of a Madagascar Elephant bird (Aepyornithidae). Also discussed are ongoing best-practice measures to both preserve this collection and render it of optimal value to users, including a brief summary of the key outside stakeholders exploiting the collection for research and other purposes. An issue of particular note is the increasing demand for tissue samples (typically 'toe-pads') from the study skins for molecular investigations - raising problematic challenges relevant to destructive sampling. Particular attention is paid to describing a recent migration of the digital database to a global standard in the form of the ‘Specify’ collection database and management tool.